تحسين جودة الخدمة لتطبيقات الزمن الحقيقي وغير الحقيقي عبر شبكة الانترنت - حجازية, محمد (Latakia University Journal -Engineering Sciences Series, 2018)
تُصنف الخدمات التي يطلبها المستخدمون عبر شبكة الانترنت إلى نوعين أساسيين، خدمات تعمل بالزمن الحقيقي مثل تطبيقات الفيديو والصوت بالزمن الحقيقي وهي تستخدم بروتوكول (UDP (Unit Datagram Protocol، وخدمات أخرى تعمل بالزمن غير الحقيقي مثل تطبيقات تصفح الويب (HTTP (Hiyber Text Transfer Protocol ونقل الملفات FTP (File Transfer Protocol) وتستخدم بروتوكول TCP( Transmission Control Protocol). يتم في هذا البحث دراسة وتحليل الخوارزميات التي تحسن جودة الخدمة لمختلف هذه التطبيقات، فمن أجل تطبيقات الزمن الحقيقي يتم استخدام قواعد الرتل التي تعطي أفضلية لهذه الخدمات وتحقق أقل تأخير زمني، أما من أجل تطبيقات الزمني غير الحقيقي فيتم دراسة خوارزميات التحكم بالازدحام التي تحقق أفضل أداء لعملية النقل الموثوق بوجود الازدحام عبر شبكة الانترنت. تم استخدام برنامج المحاكاة Opnet 14.5 لمحاكاة الخدمات المختلفة عبر شبكة الانترنت، وتبين نتائج الدراسة الحصول على أقل تأخير زمني لخدمة الصوت، وتحقيق معدل إرسال عالي لتطبيق FTP بوجود ضياع للرزم في الشبكة.Services that demanded by users via internet network are classified in two main kinds, Services work in real time such as video and voice in real time and use UDP protocol, and other services that work in non-real time such as web browsing (HTTP) and file transfer (FTP) which use TCP Protocol.In this research, we study and analyze algorithms that enhance the quality of service for various applications. For real time application, we use queues disciplines, which gives high priority for these services and achieves minimum delay. For non-real time application, we study congestion control algorithms, which achieve best performance for reliable transfer process with existing the congestion in the network. We used OPNET 14.5 program for simulating various services via internet network. Simulation results show achieving minimum delay for voice service, and achieving high transmission rate for FTP application with existing of packets loss in the network.